Disparities in curative treatments and outcomes for early stage intrahepatic cholangiocarcinoma in the United States. Issue 20 (23rd August 2022) - Lee, Yi‐Te; Singal, Amit G.; Lauzon, Marie; Agopian, Vatche G.; Luu, Michael; Noureddin, Mazen; Todo, Tsuyoshi; Kim, Irene K.; Friedman, Marc L.; Kosari, Kambiz; Nissen, Nicholas N.; Roberts, Lewis R.; et al.
Abstract : Background: Curative surgical treatments afford the best prognosis for patients with intrahepatic cholangiocarcinoma (iCCA); however, the comparative effectiveness of treatment options and factors associated with curative treatment receipt for early stage iCCA remain unknown. Methods: The authors identified patients who were diagnosed with early stage iCCA, defined as a unifocal tumor <3 cm, during 2004–2018 from the National Cancer Database. Multivariable logistic and Cox regression analyses were used to identify the factors associated with curative treatment and overall survival (OS), respectively. Results: The proportion of patients with early stage iCCA increased from 4.5% in 2004 to 7.3% in 2018, with the odds of early stage detection increasing by 3.1% per year (odds ratio [OR], 1.031; 95% CI, 1.015–1.049). Of 1093 patients who had early stage iCCA, 464 (42.5%) underwent resection, 113 (10.3%) underwent ablation, 62 (5.7%) underwent liver transplantation, and 454 (41.5%) received noncurative treatments. Hispanic patients (adjusted OR [aOR], 0.57; 95% CI, 0.33–0.97) and Black patients (aOR, 0.47; 95% CI, 0.28–0.77) were less likely to receive curative treatments than White patients. Compared with patients who underwent surgical resection, those who underwent liver transplantation had a trend toward improved OS (adjusted hazard ratio [aHR], 0.63; 95% CI, 0.37–1.08), whereas those who underwent local ablation (aHR, 1.39; 95% CI, 1.01–1.92) and noncurative treatments (aHR, 3.97; 95% CI, 3.24–4.88) experienced worse OS. Conclusions: More than one third of patients with early stage iCCA did not receive curative treatment, with Hispanic and Black patients being less likely to receive curative treatments than White patients. Surgical resection and liver transplantation were associated with improved survival compared with local ablation. Future studies should investigate disparities in curative treatment receipt and outcomes for early stage iCCA. Abstract : Greater than one third of patients with early stage intrahepatic cholangiocarcinoma fail to undergo curative treatment, with Hispanic and Black patients being less likely to receive curative treatments than White patients. Surgical resection and liver transplantation are associated with improved survival compared with local ablation.